Символ металевого казана у скіфському поховальному ритуалі крізь призму етноаналогії - Бєлопольська, О.А. (Археологія і давня історія України, 2019)
В історіографії панує традиція розглядати скіфський бронзовий казан як маркер соціуму. У статті пропонується звернутися до методу етнографічних аналогій. Поєднання етноаналогій та археологічного контексту в інтерпретації дозволяє побачити нові сакральні символи і пояснити ритуальну необхідність депонування казана у похованнях скіфів. As historiography shows, sociocultural aspect is the main perspective commonly analyzed in the interpretation of symbolic meaning of Scythian bronze cauldrons. The deposition of such vessels is typical to burials: average barrows of ordinary members of society as well as unique wealthy graves of Scythians with high social status. The hypothesis of sacral symbolic meaning of a cauldron in social perspective is primarily based on some passages by Herodotus (IV, 61 and IV, 81). These written sources merge with general context of archaeological findings — cauldrons are associated with rich grave goods.